Perancangan Ulang Interior Sdit Az Zahra Depok Dengan Pendekatan Behavior Terhadap Perkembangan Sosial Emosional Anak - Nisrina Lulu Hermawan, Kareline; Cardiah, Tita; Hambali Wilman, Reza (Telkom University, 2024)
Elementary Education in Indonesia offers various options, one of which is Islamic School. Integrated Islamic Schools (SIT) are an attractive alternative for the Muslim community in Indonesia, especially in Depok City. Integrated Islamic Schools (SIT) are quite widespread in Depok City, especially at the Elementary School (SD) level. One of them is SDIT Az Zahra Depok, which is under the auspices of the Az Zahra Education and Empowerment Foundation. This school is based on implementing moral educationn and is based on Islamic teachings, which are based on the Al-Qur’an and the sunnah of the prophet and memorization the Al-Qur’an, the requirement for graduation from this elementary school is memorizing 1 juz. Not only focusing on intellectual development, but also on the development of children’s social emotional, character and morality. Schools play an important role in shaping the personality and moral behavior of children by teaching them religious values so that they become religious people. From the programs and curriculum carried out by SDIT Az Zahra itself, rooms and facilities are neede to support the program by using a behaviorist approach to children’s social emotions. Keywords: Integrated Islamic Elementary School, behaviorism, social-emotional children.